Unleashing the potential of teacher leadership for ESD - Ghamrawi, Norma; Shal, Tarek; Ghamrawi, Najah A. R.; Abu-Tineh, Abdullah; Alshaboul, Yousef (Frontiers in Education, 2025)
This article reconceptualizes teacher leadership as a foundational pillar for advancing Education for Sustainable Development (ESD) within contemporary schooling systems. Disrupting dominant discourses that frame sustainability leadership through top-down or managerialist paradigms, the article articulates a nuanced theoretical and empirical case for recognizing teachers as ethical agents, pedagogical innovators, and transformative leaders situated at the heart of sustainability praxis. Through a critical engagement with educational leadership literature, sustainability theory, and post-structural perspectives, it interrogates the epistemic exclusions that have historically marginalized teachers in global ESD agendas. The article argues that teacher leadership, when rooted in professional agency, critical reflexivity, and contextual responsiveness, offers a powerful counter-narrative to technocratic educational reforms and opens up imaginative possibilities for cultivating just, resilient, and ecologically attuned learning communities. By reweaving the conceptual threads of sustainability, equity, and pedagogical activism, this work repositions teachers not only as implementers of policy, but as co-constructors of educational futures in an age of systemic uncertainty.